Isolation of mutations affecting the development of freezing tolerance in Arabidopsis thaliana (L.) Heynh. - Warren, G (1996)
We screened for mutations deleterious to the freezing tolerance of Arabidopsis thaliana (L.) Heynh. ecotype Columbia. Tolerance was assayed by the vigor and regrowth of intact plants after cold acclimation and freezing. From a chemically mutagenized population, we obtained 13 lines of mutants with highly penetrant phenotypes. In 5 of these, freezing sensitivity was attributable to chilling injury sustained during cold acclimation, but in the remaining 8 lines, the absence of injury prior to freezing suggested that they were affected specifically in the development of freezing tolerance. In backcrosses, freezing sensitivity from each line segregated as a single nuclear mutation. Complementation tests indicated that the 8 lines contained mutations in 7 different genes. The mutants' freezing sensitivity was also detectable in the leakage of electrolytes from frozen leaves. However, 1 mutant line that displayed a strong phenotype at the whole-plant level showed a relatively weak phenotype by the electrolyte leakage assay.